Experiences of Ghanaian frontline healthcare workers during the COVID-19 pandemic and healthcare leadership recommendations. - Kimesha Grant; Holly Sims; Alexis Carbine; Jessica Walczak; Yvonne Commodore-Mensah; Thomas Hinneh; Fred Stephen Sarfo; Lisa A Cooper; Carmen Alvarez (PLOS Global Public Health)
Understanding the experiences of frontline healthcare workers across different national and resource contexts is important for learning how to best support these providers to optimize their services during extended health emergencies. Using qualitative methods, we conducted 20 semi-structured interviews with frontline nurses and community healthcare workers to understand their working conditions, challenges, and supports during the COVID-19 pandemic. Ghana was selected as a leader in healthcare reform among African nations. Thematic analysis revealed the following themes: challenges and stressors, government support, overcoming challenges, and recommendations for leadership in healthcare organizations. Overall, healthcare workers experienced a plethora of challenges both at work and in their personal lives, including decreased access to food and medical care. They also contended with limited personal protective equipment and higher patient volumes. Despite these challenges, support from employers and the government remained limited. Participants provided several recommendations for healthcare systems and leadership to better support their workforce.